Strategi Eliminasi Praktik Korupsi pada Pelayanan Perizinan dan Pengawasan Pelaksanaan Penanaman Modal - Hanida, Rozidateno Putri; Irawan, Bimbi; Rozi, Fachrur (Integritas : Jurnal Antikorupsi, 2020)
Since the Government Regulation Number 24 of 2018 on Electronically Integrated Business Licensing Services was enacted, a gap was evidently found from two stages which potentially lead to corruption practices. Those two stages are the process of commitment fulfillment by a number of businesses and the process of the investment supervision. This study explains how the potential of corruption occur and what kind of strategies can be apllied to eliminate it. For these purposes, qualitative descriptive method was employed. Meanwhile, the data collection technique was carried out by using interview, literature study, and documentation. The result shows that the main factor causing the corruption to arise in the licensing service is the intensity of face-to-face meetings between business actors and government officials. Some fulfillment commitment activities and virtual supervision can be carried out as a strategy to eliminate this potential. Every proof and documentation that must be fulfilled by business actors such as videos, photos and etc can be submitted online.